Postappendectomy intra-abdominal abscess: a therapeutic approach. Issue 5 (May 1994) - Gorenstein, A; Gewurtz, G; Serour, F; Somekh, E
Abstract : Four hundred and sixty two children were operated on between January 1989 and June 1993 for acute appendicitis; 10 developed an intra-abdominal abscess. Intra-abdominal abscesses were accompanied by fever above 38 degrees C (nine out of 10 patients) and leucocytosis (mean leucocyte count 20.3 x 10(9)/l) and were detected sonographically four to 14 days after operation. Management included intravenous administration of antibiotics effective against both aerobes and anaerobes, and follow up with serial sonographic studies. Eight patients responded favourably to antibiotic treatment without any drainage procedure, with gradual shrinkage and collapse of abscesses. Two patients, in whom enlargement of collection was demonstrated on serial sonographic examination, eventually underwent percutaneous drainage under sonographic control. These results suggest that some paediatric patients with an intra-abdominal abscess after appendicectomy and who are followed up closely by sonography may be managed successfully with appropriate antibiotics alone.